PERCEPTIONS OF MATHEMATICS EDUCATION STUDENTS TOWARD E-LEARNING DURING THE COVID-19 PANDEMIC - Julia Noviani (KALAMATIKA Jurnal Pendidikan Matematika, 2021)
COVID-19 as a global pandemic affects various sectors, including education. This study describes students' perceptions of using e-learning in mathematics distance learning during a COVID-19 pandemic. This type of study is descriptive qualitative research. This study involved four students from the Mathematics Education Study Program, Tarbiyah, IAIN Takengon. The researcher gathered the data in this study via an interview process. The interview was conducted by phone since there was a social restriction regulation from the local government. This study states that students experience obstacles while learning mathematics using e-learning during a COVID-19 pandemic. These barriers are classified into three barriers: internal barriers, external barriers, and cross internal and external barriers. Nevertheless, the positive effects are also felt as students have independent learning, confidence while studying, motivation, ease, and flexibility in accessing the e-learning and learning contents. Furthermore, this study recommends that the e-learning design match the learning objectives to minimize the barriers.